Pecinan as an inspiration; The contribution of Chinese Indonesian architecture to an urban environment - Tjiook, Wiwi (UI Scholars Hub, 2017)
Since the abrogation of Presidential Instruction Number 14/1967 which banned Chinese customs celebrations and religion in public, there has been a revival in Chinese festivals, language, art, media, culture and not in the least in the field of architecture and urban planning. With increasing interest in heritage and the support of the Indonesian government for heritage cities programmes, several promising initiatives involving Chinese architecture have been launched in cities both large and small. A brief glance of the history of Chinese Indonesian architecture is given, as well as some recent initiatives in selected cities plus a discussion of the importance of public space in accommodating Chinese festivals. Study of old maps and photographs prompts reflections on the characteristics and development of Pecinan during the colonial era and of their later history. The analysis in this article and examples of recent developments in the cities discussed can be used as an inspiration in the revitalization of Pecinan, thereby contributing in an attractive and livable urban environment.